THE PREVALENCE OF GASTROINTESTINAL NEMATODES OF BALI CATTLE BREEDERS IN NUSA PENIDA - Antara, Putu Agus Trisna Kusuma; Suwiti, Ni Ketut; Apsari, Ida Ayu Pasti (Buletin Veteriner Udayana, 2017)
Nusa Penida is a pure breeding area of bali cattle, in which the cattle are mainly kept in conventional maintenance system and potentially infected by parasite, especially gastrointestinal nematodes. This study aims were to determine the prevalence and type of gastrointestinal nematodes in bali cattle breeders in Nusa Penida. Fecal samples were taken from 50 bali cattle breeders kept in cages (simantri) and another 50 samples were from cattle not kept in cage. The floating method was used for morphological examination and prevalence, the data was analyzed with descriptive analysis. The results showed, the prevalence of bovine gastrointestinal nematodes in Nusa Penida was 25%. The prevalence of nematode infection in bali cattle that kept cages was lower compared to the cattle that were not kept in cage. Strongyloides papillosus and Capillaria bovis were the gastrointestinal nematodes found in the infected cattle.